Characterization of Chicken IgY Specific to Clostridium difficile R20291 Spores and the Effect of Oral Administration in Mouse Models of Initiation and Recurrent Disease - Pizarro-Guajardo, Marjorie; Díaz-González, Fernando; Álvarez-Lobos, Manuel; Paredes-Sabja, Daniel (Frontiers in Cellular and Infection Microbiology, 2017)
Clostridium difficile infection (CDI) are the leading cause of world-wide nosocomial acquired diarrhea. The current main clinical challenge in CDI is the elevated rate of infection recurrence that may reach up to 30% of the patients, which has been associated to the formation of dormant spores during the infection. We sought to characterize the effects of oral administration of specific anti-spore IgY in mouse models of CDI and recurrent CDI. The specificity of anti-spore IgY was evaluated in vitro. In both, initiation mouse model and recurrence mouse model, we evaluated the prophylactic and therapeutic effect of anti-spore IgY, respectively. Our results demonstrate that anti-spore IgY exhibited high specificity and titers against C. difficile spores and reduced spore adherence to intestinal cells in vitro. Administration of anti-spore IgY to C57BL/6 mice prior and during CDI delayed the appearance of the diarrhea by 1.5 day, and spore adherence to the colonic mucosa by 90%. Notably, in the recurrence model, co-administration of anti-spore IgY coupled with vancomycin delayed the appearance of recurrent diarrhea by a median of 2 days. Collectively, these observations suggest that anti-spore IgY antibodies may be used as a novel prophylactic treatment for CDI, or in combination with antibiotics to treat CDI and prevent recurrence of the infection.